Fuzzy logic-based vector control of permanent magnet synchronous motor drives under inter-turn short-circuit fault conditions - Laamari, Y.; Boukhennoufa, N.; Benderradji, H.; Allaoui, S. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Goal. This study aims to develop and evaluate a fuzzy logic-based control strategy to enhance the fault tolerance of PMSM drives under ITSCFs conditions. Methodology. To achieve this, a mathematical model of the PMSM is developed to represent both healthy and faulty operating states. This model is integrated into a vector control framework where two types of speed controllers are compared: a conventional PI controller and a fuzzy PI controller. The proposed fuzzy logic controller is implemented within the FOC scheme and evaluated through simulation. Results. Simulation results demonstrate that the fuzzy vector control approach significantly reduces rotor speed and electromagnetic torque ripples under both healthy and faulty conditions, while maintaining stable torque output and minimizing THD. It consistently outperforms the conventional PI controller. Scientific novelty. Unlike traditional FOC methods, this study introduces a fuzzy logicenhanced control strategy specifically designed to improve PMSM performance under fault conditions. The integration of fuzzy logic with vector control offers superior dynamic response and enhanced resilience. Practical value. The proposed approach improves the robustness and reliability of PMSM drives, particularly in fault-sensitive applications such as industrial automation and electric vehicles. This contributes to extended system lifespan and improved operational stability.

Мета. Дане дослідження спрямоване на розробку та оцінку стратегії управління на основі нечіткої логіки для підвищення стійкості до відмови PMSMs в умовах ITSCFs. Методологія. Для досягнення цієї мети розроблено математичну модель PMSMs, яка описує як справні, так і несправні робочі стани. Ця модель інтегрована у систему векторного управління, де порівнюються два типи регуляторів швидкості: звичайний ПІ-регулятор та нечіткий ПІ-регулятор. Запропонований нечіткий логічний контролер реалізовано в рамках FOC схеми та оцінено за допомогою моделювання. Результати моделювання показують, що підхід з нечітким векторним управлінням значно знижує частоту обертання ротора і пульсації електромагнітного моменту як у справному, так і несправному стані, зберігаючи при цьому стабільний вихідний крутний момент і мінімізуючи сумарний THD. Він стабільно перевершує традиційний ПІ-регулятор. Наукова новизна. На відміну від традиційних FOC методів, це дослідження пропонує стратегію керування з покращеною нечіткою логікою, спеціально розроблену для покращення продуктивності PMSM в умовах несправності. Інтеграція нечіткої логіки з векторним управлінням забезпечує чудовий динамічний відгук та підвищену стійкість. Практична цінність. Пропонований підхід підвищує надійність та стійкість PMSMs, особливо у чутливих до відмов сферах, таких як промислова автоматика та електромобілі. Це сприяє збільшенню терміну служби системи та підвищенню експлуатаційної стабільності.
Keywords: permanent magnet synchronous motor; field-oriented control; inter-turn short-circuit; PI controller; fuzzy logic controller; синхронний двигун з постійними магнітами; полеорієнтоване керування; міжвиткове замикання; ПІ-регулятор; нечіткий логічний регулятор